The Noble Values of the Samin Community - Nur Wahyu Rochmadi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
The Samin community was phenomenal, because the actualization of their noble values was able to make the Dutch colonialists inconvenient, even when the Indonesian nation became independent, and the Indonesian state was established until now. The purpose of this research is to explore the noble values of the Samin people, then they are used as role models in developing the character of citizens. The research was conducted with a descriptive qualitative design. The research subjects were traditional elders, community leaders, families and other parties who had interacted with the Samin community. Data collection was carried out through observation, interviews and documentation. Data were analyzed by referring to an interactive model. The research findings explain that the noble values of the Samin community include: (a) honesty; (b) simple / prasojo; (c) extension; (d) mutual cooperation; (e) rilo, selfless, sincere; (f) friends; diligent, tenacious and painstaking; (g) ora drengki, srei, dahpen kemiren; (h) independence; and (i) fair. Based on these findings, it is suggested (1) the noble values of the Samin community be used as a reference in developing the character of citizens; and (2) character education practice must be preceded by determining the main values.